Breastfeeding doesn't need to suck : how to nurture your baby and your mental health - Kendall-Tackett, Kathleen A. (American Psychological Association, 2022)
"This book helps new mothers reach their breastfeeding goals and feed their babies with confidence. The scientific literature tells us that when breastfeeding is going well, it prompts a powerful physiological mechanism that can help minimize depression, anxiety, and PTSD"--